Methods of determination of forces in the “wheel-rail” system - Sych Tatyana; Kolomeets Andrey (MATEC Web of Conferences, 2018)
Increase in the volume of heavy traffic on railways updates the requirements for ensuring transportation safety in conditions of continuous increasing in axle loads on the track. The purpose of the study is to review methods for determining the dynamic forces arising from interaction between the wheel and the rail during rolling stock movement. The numerical method is used to determine the values of relative strain of the rail web at the transducers locations. Model verification and estimation of the calculation accuracy for several methods of determining forces in the “wheel-rail” system has been performed. Methods for determining the loads arising in the wheel and rail system, as well as the results of calculating the three load components were obtained. Simulation tests of the proposed forces control method have been performed.